Children and young adults with spinal muscular atrophy treated with nusinersen. (January 2021) - Osredkar, Damjan; Jílková, Markéta; Butenko, Tita; Loboda, Tanja; Golli, Tanja; Fuchsová, Petra; Rohlenová, Marie; Haberlova, Jana
Abstract: Introduction: Treatment of children with spinal muscular atrophy (SMA) now includes disease modifying drugs such as nusinersen. Real-world data can provide new insight on the efficacy and safety of nusinersen for treatment of children with SMA. Aim: The aim of our study is to evaluate the effect of treatment of children and young adults with SMA type I, II and III at various stages of the disease after 14 months of treatment with nusinersen. Methods: In this prospective, two-center (in Slovenia and Czech Republic) study, data from all patients with a genetically confirmed diagnosis of SMA before 19 years of age who were treated with nusinersen were collected before initiation of treatment, and after 6 and 14 months of treatment. Various standardized motor scales and a questionnaire that focused on daily-life activities were used. Results: Form both centers, 61 patients from 2 months to 19 years of age were enrolled in the study. Sixteen had SMA type I (median age 5.2 years); 32 had SMA type II (median age 8.9 years); and 13 had SMA type III (median age 8.6 years). Patients had 2-4 copies of the SMN2 gene. One patient died in the study period and one discontinued treatment. After 14 months of treatment, SMA type I (p = 0.002) and type II (p = 0.002) patients had significantly better outcomes, while type III patients showed a trend towards improvement (p = 0.051) on motor scales. Younger age at the initiation of treatment and a higher number of SMN2 copies is related to a better outcome. Younger children also seem to improve faster compared to older children. No serious side effects were reported. Conclusion: The results of our study which included patients of various SMA types and stages of the disease suggest that treatment with nusinersen benefits patients, regardless of SMA type. Earlier age at the initiation of treatment and a higher number of SMN2 copies were related to a better outcome, however even some patients of higher age and/or later stage of the disease benefited from the treatment. Our study also suggests that nusinersen is safe to use, as no major side effects, requiring discontinuation of treatment, were reported. There is an unmet need for novel standardized tests and biomarkers, which could help guide clinician's decisions on the selection of best treatment options and monitor treatment success. Highlights: Treatment with nusinersen benefited patients with SMA of all types. Earlier age at the initiation of treatment and a higher number of SMN2 copies were related to a better outcome. Patients of higher age and/or later stage of the disease benefited from the treatment as well, although to a smaller extent.